Infrastructure and foreign trade elasticities: empirical evidence for China - Souza Fraga, Jefferson; Lara Ferreira-Filho, Helder (Brazilian Keynesian Review, 2022)
This article investigates the effect of infrastructure on the income elasticities of exports and imports for the Chinese economy, in the period 1981-2016, employing the Bayesian Model Averaging (BMA) technique. The results suggest that a better infrastructure promotes an increase in the income elasticity of exports and a decrease in the income elasticity of imports. The control variables – exchange rate, human capital, government consumption and institutional quality – increase the income-elasticity of exports, but have mixed results with respect to the income-elasticity of imports. Income elasticities were estimated applying the Kalman filter, which allows to obtain a time-varying estimate of the equilibrium growth rate of the balance of payments. Finally, the results show that infrastructure has a positive and significant long-term impact on the ratio of foreign trade elasticities in the Chinese economy.